Examining mobile learning adoption: The role of ease of use, usefulness, and intention - Sulistiowati Sulistiowati (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
The proliferation of mobile-based learning apps on the Google Play Store has been facilitated by the advancement of information technology. However, the level of optimal use is still a challenge with several problems related to: 1) Perceived Ease of Use (PEU), 2) Perceived Usefulness (PU), 3) Behavioral Intention (BI), 4) Use Behavior (UB). Therefore, this study aims to analyze the factors that influence the acceptance (UB) of mobile-based learning applications using the Technology Acceptance Model (TAM). This model uses the variables PEU, PU, ​​BI, and UB. Data were collected through an online questionnaire with 107 respondents and analyzed using SEM-PLS. The results showed that PEU had a significant effect on PU (62.8%), but did not directly affect BI and UB. PU had a significant effect on BI (50.3%) and did not directly affect UB. While BI had a significant effect on UB (44.9%). This finding confirms that ease of use of an application (PEU) must go through usefulness (PU) to be able to influence user intention (BI), then BI influences UB or in other words BI mediation plays a very important role in bridging the influence of initial perceptions on actual use. The implications of this study can help developers of mobile-based learning applications to increase user engagement so that the application can be accepted and used by users.